Collective effects in light scattering from cold strontium clouds - Moriya, Paulo Hisao (2016)
A cold atomic cloud is a versatile object, because it offers many handles to control and tune its properties. This facilitates studies of its behavior in various circumstances, such as sample temperature, size and density, composition, dimensionality and coherence time. The range of possible experiments is constrained by the specifications of the atomic species used. In this thesis presents the work done in the experiment for laser cooling of strontium atoms, focusing on its stability, which should provide cold and ultracold samples for the study of collective effects in light scattering. From the initial apparatus, innumerous changes were performed. The vacuum system got improved and now reached lower ultra high vacuum due to the pre-baking done to its parts and adding a titanium-sublimation stage. The quadrupole trap were improved by the design and construction of a new pair of coils. The stability of the blue, green and red laser systems and the loss prevention of laser light were improved, giving rise to a robust apparatus. Another important point is the development of homemade devices to reduce the costs and to be used as a monitor of different parts of an cold atoms experiment. From this homemade devices, we could demonstrate a dramatic linewidth narrowing by injection lock of an low cost 461 nm diode laser and its application to our strontium experiment. In the end, this improved experimental apparatus made possible the study of a new scattering effect, the mirror assisted coherent back-scattering (mCBS).